2010
DOI: 10.1016/j.jfms.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid stimulation with recombinant human thyrotropin in healthy cats, cats with non-thyroidal illness and in cats with low serum thyroxin and azotaemia after treatment of hyperthyroidism

Abstract: This study investigated the recombinant human thyrotropin (rhTSH) stimulation test in healthy cats (group 1), cats with non-thyroidal illness (group 2) and cats with low serum total T(4) (TT(4)) and azotaemia after (131)I treatment (group 3). Serum TT(4) responses and thyroidal pertechnetate uptake after administration of 25 microg rhTSH IV were assessed. Baseline serum TT(4) was significantly lower in group 3 compared with group 1, but not between other group pairs. Serum TT(4) increased significantly in grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
1
9
1
Order By: Relevance
“…Thyroid hormone replacement therapy is associated with an improvement in renal function in canine patients with primary hypothyroidism2; however, 1 small previous study reported that restoration of euthyroidism in radioiodine‐treated cats with iatrogenic hypothyroidism and azotemia did not improve GFR 3. In the present study, restoration of euthyroidism in cats with iatrogenic hypothyroidism resulted in a decrease in plasma creatinine concentrations in 18 of 19 cats, and resolution of azotemia in 50% of hypothyroid azotemic cats.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Thyroid hormone replacement therapy is associated with an improvement in renal function in canine patients with primary hypothyroidism2; however, 1 small previous study reported that restoration of euthyroidism in radioiodine‐treated cats with iatrogenic hypothyroidism and azotemia did not improve GFR 3. In the present study, restoration of euthyroidism in cats with iatrogenic hypothyroidism resulted in a decrease in plasma creatinine concentrations in 18 of 19 cats, and resolution of azotemia in 50% of hypothyroid azotemic cats.…”
Section: Discussioncontrasting
confidence: 62%
“…Thyroid hormone replacement treatment is associated with an improvement in renal function in dogs with primary hypothyroidism2; however, the effect of restoration of euthyroidism on renal function in cats with iatrogenic hypothyroidism has only been investigated in 1 small previous study of cats that had been treated with radioactive iodine, which demonstrated no improvement in glomerular filtration rate (GFR) 3…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The indications, protocol, and interpretation of the TSH stimulation test are similar for the cat and dog except that a lower dose of recombinant human thyrotropin (rhTSH) (25 micrograms IV) is used in the cat (Stegeman et al, 2003;van Hoek et al, 2010). In euthyroid cats, there is a two-to threefold increase in total T 4 6 to 8 hours after TSH administration.…”
Section: Thyroid-stimulating Hormone Stimulation Testmentioning
confidence: 99%
“…A thyroid panel including T4 and TSH, preferably supplemented by free T4 and T3, in combination with typical clinical signs is required to diagnose feline hypothyroidism. A thyrotropin releasing hormone (TRH)-or TSH-stimulation test can also be performed to confirm the diagnosis [37]. In the present case a TSH-stimulation test was not performed, because the clinical and radiographic findings in combination with a low T4 value and a high TSH were regarded as an adequate basis to diagnose the disease.…”
Section: Discussionmentioning
confidence: 94%